Characterization of semi-refined carrageenan reinforced with cellulose nanofiber incorporated α-tocopherol for active food packaging applications - Wan Yahaya, Wan Amnin; Raja Ahmad, Raja Nurliyana; Mohd Azman, Nurul Aini (Trans Tech Publications Ltd, Switzerland, 2020)
This work focuses on the development of biodegradable active films packaging using natural compounds by reducing the plastic waste to environment but also as a potential substitute of synthetic preservative in food. Active film packaging was formulated using semi-refined carrageenan (SRC) biopolymer plasticized with glycerol (G), reinforced with different concentrations cellulose nanofiber (CNF) at 0 to 13% w/w incorporated 0.4% w/w α-tocopherol as natural antioxidants. Physical and mechanical properties of the film samples were analyzed. Active films reinforced CNF enhanced overall the tensile strength and the value of elongation at break significantly (p<0.05). Film samples reinforced with 10% w/w CNF improved the value of opacity, thickness, films solubility (%) and moisture content (%) with (5.60±0.14, 0.139 ±0.02, 27.89±2.41 and 18.88±1.06) respectively. In summary, an active film with 10% w/w CNF showed highest improvement on the mechanical and physical properties due to the uniform dispersion between CNF-SRC matrix interactions. Hence, the new formulation of active packaging film with showed competitive properties that could be an alternative solution for biodegradable films with function of food protection against oxidative degeneration.